Halalan toiyyiban food handling practices: a review on street food vendors in Malaysia - Piee @ Shafiee, Nor Faradillah; Ab Karim, Muhammad Shahrim; Mohamed Razali, Abu Bakar; Ungku Zainal Abidin, Ungku Fatimah (Academic Inspired Network, 2017)
The street food sector has become an important component of food distribution system in many cities in Malaysia particularly for midday meals. However, certain street-vended food can pose significant risk to consumers due to microbiological contamination. The concern of hygiene and halal become critical for Muslim consumers and also non-Muslim consumers in Malaysia. Thus, this paper aims to determine the matters of halalan toyyiban among street food vendors in a way to guarantee the food being serve to patron is safe and fit for consumption. Halal status is a certification awarded based on the application of food service operators to be certified. Currently, there is no certification made for the off-premise outlet such as street food vendors. Nevertheless, without the halal certification, it does not mean that they are the excluded group to practice halal and toyyib especially among Muslim vendors. Halal status is not only about the halal ingredients or halal sources but as well as the process of the whole food preparation should be following the halalan toyyiban practice. It is in line with the holistic concept of halalan toyyiban ‘from farming to fork’. This paper is using review analysis based on previous articles that has been done by other researchers. Literature review was conducted to gather all information of street food vendors. Based on the information gather, the concept of halalan toyyiban will recommend hoping to serve better food for Muslim community who consume the food and nurture the awareness of Muslim vendors to practice halalan toyyiban in their business. Thus, this paper will contribute to the body of knowledge in the technical